Aesthetic and colorful: Dichroic polymer solar cells using high-performance Fabry-Pérot etalon electrodes with a unique Sb2O3 cavity. (November 2020) - Yeom, Hye Rim; Song, Seyeong; Park, Song Yi; Ryu, Hwa Sook; Kim, Jae Won; Heo, Jungwoo; Cho, Hye Won; Walker, Bright; Ko, Seo-Jin; Woo, Han Young; Kim, Jin Young
Abstract: Semitransparent organic solar cells (STOSCs) are a technology that combines the benefits of visible light transparency and light-to-electrical energy conversion. One of the greatest opportunities for STOSCs is their integration into windows and skylights in energy-sustainable buildings. For this application, the aesthetic aspects of solar cells may be as important as their electrical performance. Here, our strategy enables to achieve high-quality and colorful STOSCs using Fabry-Pérot etalon-type electrodes. These electrodes are composed of an antimony oxide (Sb2 O3 ) cavity layer and two thin Ag mirrors. These dichroic tri-layer structures perform two functions as top conducting electrodes and color filters. These dual-function electrodes were applied to photovoltaic devices and displayed vivid colors, natural transparency, and good performance as compared to devices that use conventional metal electrodes. Furthermore, to achieve saturated colors and low photocurrent losses, active layer materials were selected such that their transmittance peaks matched the transmittance maxima of the electrodes. These strategies for colorful STOSCs result in power conversion efficiencies (PCEs) of up to 13.3% and maximum transmittances ( T MAX ) of 24.6% in blue devices, PCEs of up to 9.71% and TMAX of 35.4% in green devices, and PCEs of up to 7.63% and T MAX of 34.7% in red devices. Graphical abstract: Image 1 Highlights: High-quality and colorful semitransparent organic solar cells were demonstrated. Fabry-Pérot etalon electrodes are composed of Ag/Sb2 O3 /Ag. These electrodes functioned dually as top conducting electrodes and color filters. Photocurrent losses were effectively minimized with the same-colored active layers. 13.3% of power conversion efficiency was achieved in blue semitransparent devices.